Do Forest Fires Make Biotic Communities Homogeneous or Heterogeneous? Patterns of Taxonomic, Functional, and Phylogenetic Ant Beta Diversity at Local and Regional Landscape Scales - Arnan, Xavier; Cerdá, Xim; Rodrigo, Anselm (Frontiers in Forests and Global Change, 2020)
Biotic homogenization—the erosion of biological differences among ecosystems due to human disturbance—is a pervasive threat to forest landscapes given the current global biodiversity crisis. In Mediterranean forests, wildfire is a particularly common disturbance that affects biodiversity at local, regional, and global scales. However, little is known about how fire influences biotic homogenization. We analyzed the taxonomic, functional, and phylogenetic β-diversity of ground-dwelling ant communities across a large region in the Mediterranean. We tested the hypothesis that fire leads to community heterogenization at the local landscape scale but community homogenization at the regional landscape scale. We sampled ant communities in 5 pairs of burned and unburned plots at 21 study sites (n=210 plots) representing seven forest types in Catalonia (northeastern Iberian Peninsula). Ant species were characterized based on 10 functional traits and phylogenetic relatedness. We then calculated taxonomic, functional, and phylogenetic community dissimilarity indices at local and regional landscapes scales focusing on common versus rare species. Our results show that fire strongly affected community dissimilarity at the local landscape scale. Regardless of diversity type or species type, community dissimilarity was always greater among burned and unburned plots combined than among unburned plots alone, a pattern that was largely driven by Pinus nigra forests, Quercus ilex forests, and shrublands composed of resprouter species. At the regional landscape scale, community dissimilarity was the same among burned and unburned plots and among unburned plots. However, when we examined taxonomic data for common species and phylogenetic data for rare species, community dissimilarity was slightly lower among burned plots than it was among unburned plots and among burned and unburned plots. Fire clearly affected the degree of biotic homogenization within ant communities, and these effects depended on spatial scale, local vegetation type, diversity type, and species type. Overall, our results suggest that, in Mediterranean regions composed of diverse forest types, wildfire generates local environmental heterogeneity and, as a consequence, locally heterogeneous ant communities. These effects are more dramatic in forest types where fire increases habitat openness. At the regional scale, fire does not create heterogeneity, but might even render ant communities more homogeneous.